Preliminary study of Liquid Air Energy Storage integrated with LNG cold recovery. (February 2019) - She, Xiaohui; Peng, Xiaodong; Zhang, Tongtong; Cong, Lin; Ding, Yulong
Abstract: Liquid Air Energy Storage (LAES) attracts much attention to smooth the intermittency of renewable energy and shift the peak load. LAES has many advantages, such as large energy storage density, no geographical constraints, fast response, etc. However, it has a lower round trip efficiency (~50%), compared with other large-scale energy storage technologies (~70%). Based on our previous research, there is a large amount of compression heat which is excess in the LAES. On the other hand, the liquified natural gas (LNG) releases much high-grade cold energy which is usually wasted in the LNG station. Therefore, there is a good integration point between the LAES and LNG. This paper uses the excess compression heat in the LAES and the wasted cold energy in the LNG to drive a Brayton cycle for power generation (denoted as LAES-LNG). The simulation results show that the LAES-LNG system could achieve a high round trip efficiency at ~72%, which is ~31% higher than the baseline LAES and is comparable with other large-scale energy storage technologies. The LAES-LNG system enhances the competitiveness of the LAES and promotes its wide application.